MENGUNGKAP TINDAK PIDANA KORUPSI DARI PEMBUKTIAN TERBALIK DAN LAPORAN HARTA KEKAYAAN PENYELENGGARA NEGARA (LHKPN) - Mangisi Simanjuntak (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
In a formal criminal law system of Indonesia , especially the Code of Criminal Procedure , it is understandable that the burden of proof regarding the existence of criminal offenses committed by the accused is on the Prosecution . In its development , the burden of proof which was originally in the hands of the Prosecution and then shifted to the defendant the burden particularly on corruption. In this case the defendant claimed that he played an active role not as a criminal . The defendant in the courtroom that will make all the burden of proof and if it can not prove the defendant was found guilty of committing a crime . This concept was later called by the reversal of the burden of proof ( the reversal burdenof proof)